Aum Shinrikyo, Al Qaeda, and the Kinshasa Reactor : implications of three case studies for combating nuclear terrorism - Daly, Sara A.; Parachini, John.; Rosenau, William; Rand eBooks (Santa Monica, CA : RAND, 2005)
Revelations about A.Q. Khan's global nuclear marketing efforts and Osama bin Laden's contact with Pakistani nuclear scientists have raised concerns about terrorist acquisition of a nuclear or radiological weapons capability. Such a capability would pose a grave danger to U.S. national security and also to the security of the international system of nation-states. Looking across three case studies, this documented briefing concludes with a set of observations. First, access to significant resources, including the sanctuary of a state, will not guarantee the success of a nonstate actor's nuclear acquisition effort. Second, even sophisticated terrorists, searching for nuclear material, have been victims of scams. Third, Russian officials appear to have been less corrupt, and Russian nuclear materials and expertise more secure than many analysts in the West have alleged. Fourth, despite inspections and safeguards, the IAEA failed to prevent the loss of reactor fuel. Finally, the study suggests that strict control s on nuclear weapons, materials, and expertise will reduce opportunities for terrorists to acquire these resources.
"RAND Project Air Force."
Includes bibliographical references (p. 71-75).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Oumu Shinrikyō (Religious organization); Qaida (Organization); Deterrence (Strategy); Nuclear arms control; Nuclear terrorism -- United States -- Case studies; Nuclear weapons; Terrorism -- Prevention -- Case studies; Electronic books